Ship design for efficiency and economy - Schneekluth, H. (Herbert) 1921-
The previous edition of Ship Design for Efficiency and Economy was published as a Butterworth's marine engineering title. It has now been completely revised and updated by Schneekluth and Bertram. This book gives advice to students and naval architects on how to design ships - in particular with regard to hull design. The previous edition of this book was published in 1987. Since then, there have been numerous important developments in this area and the new additions to this book reflect these changes. Chapter 3 has been completely rewritten with added information on methodology of optimizatio.